Mobile sensing in psychology: methods and applications - Mehl, Matthias R.; Eid, Michael; Wrzus, Cornelia; Harari, Gabriella M.; Ebner-Priemer, Ulrich (The Guilford Press, 2024)
"The possibilities mobile sensing opens up for the social, behavioral, biomedical, and life sciences appear almost infinite and are bound to become even more comprehensive in the years to come. However, data collection with new information technology also poses new challenges for research and applied fields. Is everything that is possible also legally allowed? What are the personal and societal consequences of the possible deep insights into very private areas of life for research ethics and the relations between the researchers and those being researched? How can data be stored so that anonymity and privacy are preserved? How can quality criteria be formulated for this new and rapidly developing field of research? And how can we ensure that information and predictions derived from mobile sensing are psychometrically accurate and practically useful as we move from scientific proof-of-concept measurements to medical/clinical measurements that aim at supporting and improving the diagnostic process? This handbook answers these questions and based on the conviction that a profound understanding and the sound application of mobile sensing methods require specific knowledge and competencies: scientific background and the key concepts, how to generally plan and conduct a mobile sensing study, different methods of data collection with mobile sensing, both in terms of the technological know-how and the methodological how-to, and possibilities and limitations of mobile sensing and of best-practice examples from different areas of application"--
Literaturangaben
Keywords: Methode; Mobiles Endgerät; Psychologie